Veils, turbans, and Islamic reform in northern Nigeria - Renne, Elisha P. (African expressive cultures, 2018)
Inhaltsverzeichnis: Material religion and Islamic reform in northern Nigeria -- Islamic dress, textile production, and trade in the time of the Sokoto Caliphate -- Muslim identity, Islamic scholarship, and cloth connections in Ilorin -- The Sardauna's turbans -- Veiling, gender, and fashion -- Performing pilgrimage : worship and travel, textiles and trade -- Marks of progress : Islamic reform and industrial textile production in Kaduna -- Failures of modernity and Islamic reform : dress and deception in northern Nigeria in the 21st century -- Epilogue. Moral imagination, material things, and Islamic reform.